5th International Meeting of Early-stage Researchers in Palaeontology - Spiridonov, Andrej; Dankina, Darja; Daumantas, Liudas (Vilnius University Proceedings, 2021)
The International Meetings of Early-stage Researchers in Palaeontology (IMERP) are aimed at early-stage palaeontologists, from undergraduate students to recent post-doctoral researchers. Geologists, biologists or any scientist with research topics related to palaeontology, as well as palaeoartists, are also welcome.The IMERP has two main objectives:To provide a friendly environment for early-stage researchers to present their research through oral or poster presentations and follow each other’s progress.To share new methods and ideas useful in palaeontology, and develop the skills of the attendees with the help of leading experts, invited to give lectures about their fields.The IMERPs are usually held in villages or towns located in countryside areas of geological interest. This way the meeting can be held in a closer and more friendly environment, as well as help to the dissemination of the regional natural heritage among the local population. A field trip to this paleontological and geological heritage is offered to the meeting participants.After the 1st IMERP in 2016, the 2nd IMERP was held in Sigri (Lesbos, Greece) in 2017, the 3rd IMERP in Krasiejów (Opole, Poland) in 2018, and the 4th in Cuenca (Spain) in 2019
Keywords: fossils; palaeontology; palaeoenvironment; palaeoclimate; palaeoecology